Agricultural Branding: Nine Routes - Bambang Sukma Wijaya (Jobmark: Journal of Branding and Marketing Communication, 2021)
As an enduring sector, agriculture requires new approaches to develop and communicate its values to remain relevant and meaningful. Agricultural branding is a powerful alternative solution amid a thriving agricultural industry, business, and technology. This article paves the way for agricultural branding strategies and studies by providing nine routes to explore: 1) agricultural policies and programs, 2) production and commodities, 3) distribution and services, 4) consumption and accessibility, 5) agricultural communication and education, 6) culture and resources, 7) investment and sustainability, 8) collaboration and diversification, and 9) technology and innovation. This article is helpful as a reference for academic research and an insightful resource for professional practitioners and industry in developing a more advanced agricultural sector.